Hanukkah upside down - Weissman, Elissa Brent (Abrams Books for Young Readers, 2023)
From their homes in New York and New Zealand, cousins Noah and Nora have a competition to decide who can have the world's best Hanukkah, winter or summer, but as the eight nights of Hanukkah go on, they realize they have more in common than they thought.